3t-1=11t-65

Simple and best practice solution for 3t-1=11t-65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-1=11t-65 equation:


Simplifying
3t + -1 = 11t + -65

Reorder the terms:
-1 + 3t = 11t + -65

Reorder the terms:
-1 + 3t = -65 + 11t

Solving
-1 + 3t = -65 + 11t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-11t' to each side of the equation.
-1 + 3t + -11t = -65 + 11t + -11t

Combine like terms: 3t + -11t = -8t
-1 + -8t = -65 + 11t + -11t

Combine like terms: 11t + -11t = 0
-1 + -8t = -65 + 0
-1 + -8t = -65

Add '1' to each side of the equation.
-1 + 1 + -8t = -65 + 1

Combine like terms: -1 + 1 = 0
0 + -8t = -65 + 1
-8t = -65 + 1

Combine like terms: -65 + 1 = -64
-8t = -64

Divide each side by '-8'.
t = 8

Simplifying
t = 8

See similar equations:

| 2t+20=11t-79 | | -1.1=3.9-5y | | 34=5 | | 36/12x3^2= | | -4(6-b)=4 | | 14x-4+6x-14=180 | | 15x^2-84xy-36y^2=0 | | 16-14=x/-8 | | 18(4-207)=d | | .6=.2+3x | | 12t+-23=7t+2 | | j-12.5=39.04 | | -9N-5+2N+6= | | 10x+25y=505 | | 3w-10w=-49 | | 5-2(4-7)= | | 4(z-6)=9(z+4) | | 6t+69=11t+14 | | (x+1)*31=50 | | -40/3=40/3x | | 14x+20=4(3x+7)+2x-8 | | -8(.5y-3)=3 | | -2d+6d-5+9= | | 20=6n | | 5(r+6)=5(r+4) | | 5(x+1)=6(x-6) | | -7(2x-5)+9=-14x+44 | | 2y(y+3)+5(y-3)=36 | | 6(x-6)=5(x-9) | | 4a^2+8a-32=0 | | .400(13.80-23.50)=x | | 6(2x-4)=5(x-9) |

Equations solver categories